The Change of Land Cover and Biocapacity of CO2 Gas Emission Absorption in Gresik Urban Area - Ghozali, Achmad; Nurrahman, Fery Irfan; Santoso, Eko Budi (SPECTA Journal of Technology, 2017)
Gresik urban area is dominated by industrial, housing, trade and services activities. The growth of activities contributes to the land use change from green open spaces into built-up areas. The impact of land use change influence the level of air pollution and CO2 gas emission in Gresik urban area. The previous study briefly shows that this urban area produces 50.37% of the total CO2 gas emissions. The production of CO2 gas emissions should be controlled to reduce the impact of climate change in urban areas such as increasing urban temperature, hydrological cycle anomaly, drought, land degradation and other social and environmental issues. The green open space can recycle the CO2 gas emissions and can increase the absorption capacity of the CO2 gas emissions (bio-capacity). The land cover change for built-up area potentially reduces the absorption of CO2 gas emissions in Gresik urban area. Therefore the identification of the land cover change on CO2 emission absorption becomes an objective of this study. The preliminary study can formulate the strategic steps in the development of Gresik urban area that supports urban greenery and adaptive effort to respond the climate change. The study is conducted in two steps. The first step is to analysis the land cover change based on the Landsat satellite imagery analysis. The second step is to measure the dynamic change of the region's ability(bio-capacity) to absorb CO2 emissions by using ecological footprint analysis. The results show that Gresik urban area has a high development of developed land to the North area, Manyar Sub District. The growth of the developed land is more converting the fishpond land. The green areas in this regiontend to be influenced by farming activities which also convert into fishpond land. Bio-capacity of CO2 gas emission absorption increases from 2003 of 3.548 gha to 5.656 gha but the comparison between bio-capacity of CO2 gas emission absorption and developed land shows the declining tendency in each year. In 2003, the comparison score is 1.59 gha/ha of developed land. In 2014, the score is declining into 1.48 gha/ha or developed land.